2008
DOI: 10.1111/j.1747-4477.2007.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of different reciprocating systems used during endodontic retreatment

Abstract: The present study evaluated the effectiveness of two reciprocating systems for the removal of root-filling material during endodontic retreatment. One hundred extracted mandibular premolars were prepared and root-filled with gutta-percha and sealer. Root fillings were removed with K-files according to the following techniques: Group A--hand instrumentation; Group B--Endo-Gripper system driven by compressed air; Group C--INTRAmatic 29CH + INTRA-LUX 3LD driven by compressed air; Group D--Endo-Gripper system driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 10 publications
2
21
0
4
Order By: Relevance
“…This is consistent with the findings of other studies (4,5,15,19) and was observed in both radiographic and microscopic analysis of samples. The apical third is a critical zone, requiring a considerable enlargement when cleaning and shaping the canals (20).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with the findings of other studies (4,5,15,19) and was observed in both radiographic and microscopic analysis of samples. The apical third is a critical zone, requiring a considerable enlargement when cleaning and shaping the canals (20).…”
Section: Discussionsupporting
confidence: 82%
“…The choice of using a solvent in this study considered the existing literature (1,2,7,9,10,18) and the clinical relevance as it attempted to mimic genuine clinical situations that demand solvation. Some studies reported favorable results with the use of solvents to remove gutta-percha (17,19).…”
Section: Discussionmentioning
confidence: 99%
“…The consistently lower number of completely clean root canals at 2 mm compared with the other levels of the root may be explained by the difficulty of both instruments to work efficiently beyond the curvature of the root canal. This is in agreement with many studies that found that the apical part is the most difficult to clean (16)(17)(18).…”
Section: Discussionsupporting
confidence: 94%
“…For the NiTi instruments, filling removal in the cervical third was facilitated by dental anatomy in this region and speed of rotary instruments. Perhaps plasticization of gutta-percha caused by the temperature increase produced by the automated systems facilitated its removal from the coronal third, which is the area that concentrates the greatest filling volume (27). However, several studies have found that NiTi instruments are not more effective than hand instruments in removing filling material from the canal walls (19-22, 28, 29).…”
Section: Discussionmentioning
confidence: 98%